A coupled dynamic cohesive zone model for FRP-concrete mixed-mode separation. (15th July 2021) - Li, Gen; Tan, Kang Hai; Fung, Tat Ching; Yu, Qing Jun; May, Michael
Abstract: Cohesive zone models (CZMs) have been used to model composite fracture, metal adhesion failure, concrete cracking and other fracture scenarios. In these applications, CZMs are broadly classified into uncoupled models for pure mode fracture and coupled models incorporating mode I and mode II characteristics for mixed-mode fracture. Various coupled dynamic CZMs have been provided for dynamic fracture problems. However, a coupled CZM for FRP-concrete bond interface is still lacking. Such a bond interface contains diverse traction-separation performance in mode I and mode II fracture, as well as dynamic enhancing effect. To bridge this gap, current study proposed a coupled dynamic CZM to analyse FRP-concrete mixed-mode separation. The main objective was to evaluate model response under various mixed-mode ratios, including stress-separation curves and energy dissipation. The model was validated by various FRP-concrete dynamic separation tests, e.g. single-lap shear tests, three-point bending tests and FRP strengthened reinforced concrete (RC) beam subjected to a dynamic loading. Subsequently, the model was applied in finite element analysis (FEA) of an FRP strengthened RC wall under blast scenarios. From the comparison with the test results, the model was shown to be reliable and accurate in simulating the behaviour of FRP-concrete mixed-mode separation.